Answer:
A) f^-1(x)=(x-8)^3+2
Step-by-step explanation:
To find the function inverse, switch the x with y and solve for y.
![y=\sqrt[3]{x-2}+8 \\\\x=\sqrt[3]{y-2}+8\\\\(x-8)^3 = y-2\\\\ (x-8)^3 + 2 = y](https://tex.z-dn.net/?f=y%3D%5Csqrt%5B3%5D%7Bx-2%7D%2B8%20%5C%5C%5C%5Cx%3D%5Csqrt%5B3%5D%7By-2%7D%2B8%5C%5C%5C%5C%28x-8%29%5E3%20%3D%20y-2%5C%5C%5C%5C%20%28x-8%29%5E3%20%2B%202%20%3D%20y)
Answer:
71
Step-by-step explanation:
I don't understand what you are trying to say
Answer:
the second one
Step-by-step explanation:
it is not 2/3 because it is 1/2
Answer:
a =13/5
Step-by-step explanation:
f(x) = 6x − 5
f(5a) = 6*5a − 5=73
30a -5 = 73
Add 5 to each side
30a -5+5 = 73+5
30a =78
Divide by 30
30a/30 = 78/30
a =13/5